New species of the plant bug genus Neolygus Knight from Japan, Taiwan and Thailand (Hemiptera: Heteroptera: Miridae: Mirini) - Yasunaga, Tomohide (Zootaxa, 2024)
Ten new species of the Holarctic-Oriental mirine genus Neolygus Knight are documented, on the basis of specimens collected from eastern Asia and the Oriental Region: N. autumnus n. sp., N. chichibumontis n. sp., N. chikanoshima n. sp., N. hasegawai n. sp. and N. yonanus n. sp. (Japan); N. babai n. sp., N. formosaroseus n. sp., N. fuscovultus n. sp. and N. rufifemoratus n. sp. (Taiwan); and N. chaiyaphum n. sp. (Thailand). The generic characters are discussed, and a Japanese taxon, Neolygus tsugaruensis (Yasunaga, 1992), is herein proposed as a junior synonym of N. roseus (Yasunaga, 1991). Updated key to Japanese species and checklist of the Old World congeners are also provided.